Upaya Sekolah dalam Merajut Kebersamaan di Tengah Perbedaan Agama sebagai Misi yang Dialogis: Studi di SMA Negeri 1 Sumbul, Dairi, Sumatera Utara (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to examine how schools foster togetherness amid religious diversity through a dialogical approach. This research employed a qualitative method and was conducted at SMA Negeri 1 Sumbul. Data were collected through observation, interviews, and documentation, while the analysis used the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The findings reveal that three main religions Islam, Catholicism, and Protestantism coexist harmoniously within the school due to strong practices of tolerance. This is reflected in the implementation of religious worship conducted simultaneously at the same time but in different places according to each belief, as well as mutual respect during religious celebrations such as Ramadan and Eid al-Fitr, Easter, and Christmas. In addition, social interactions among students occur in an open, communicative, and non-discriminatory manner. These findings indicate that schools play a significant role in promoting unity through multicultural education, religious moderation, and dialogical approaches. Therefore, schools can serve as effective spaces for shaping students’ tolerant character and their ability to live harmoniously in a diverse society.